Development of a Low-Cost Wire Arc Additive Manufacturing System - Miguel Navarro; Amer Matar; Seyid Fehmi Diltemiz; Mohsen Eshraghi (Journal of Manufacturing and Materials Processing, 2021)
Due to their unique advantages over traditional manufacturing processes, metal additive manufacturing (AM) technologies have received a great deal of attention over the last few years. Using current powder-bed fusion AM technologies, metal components are very expensive to manufacture, and machines are complex to build and maintain. Wire arc additive manufacturing (WAAM) is a new method of producing metallic components with high efficiency at an affordable cost, which combines welding and 3D printing. In this work, gas tungsten arc welding (GTAW) is incorporated into a gantry system to create a new metal additive manufacturing platform. Design and build of a simple, affordable, and effective WAAM system is explained and the most frequently seen problems are discussed with their suggested solutions. Effect of process parameters on the quality of two additively manufactured alloys including plain carbon steel and Inconel 718 were studied. System design and troubleshooting for the wire arc AM system is presented and discussed.